1990
DOI: 10.1111/j.1365-3040.1990.tb01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of alpine and non‐alpine Aquilegia species to increased ultraviolet‐B radiation

Abstract: Two species of columbines, Aquilegia caerulea (which lives in alpine environments) and A. canadensis (a lower-elevation species) responded to artificially increased levels of solar UV-B radiation by becoming significantly shorter and developing a significantly greater number of leaves. The degree of shortening was greater in A. canadensis, the nonalpine species, while the number of leaves increased faster in A. caerulea. Significant differences in gashandling and water-use physiological responses were noted, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…1, Table 1). Similarly, in Aquilegia subjected to u.v.-B enhancement, the concentrations of u.v.-screening alkaloids have been reported to diminish, whilst those of flavonoids increased (Larson, Garrison & Carlson, 1990). …”
Section: Resultsmentioning
confidence: 99%
“…1, Table 1). Similarly, in Aquilegia subjected to u.v.-B enhancement, the concentrations of u.v.-screening alkaloids have been reported to diminish, whilst those of flavonoids increased (Larson, Garrison & Carlson, 1990). …”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the full community exhibited the smallest responses to UVB (Figure 2). Reports that algal species originally isolated from high-UV radiation locations (Larson et al, 1990;Rautenberger et al, 2013) and marine organisms from the Southern Hemisphere that are subject to higher UVB radiation (Agustí et al, 2015) are particularly resistant to UVB radiation indicate that the history of UV radiation experienced by different taxonomic groups may also account for their diverse responses to UVB radiation. Furthermore, sensitivity to UVB will also imply other aspects than those analyzed in this metaanalysis, as it is expected some responses should be not related to phylum but show large variability among species within the same phylum (e.g., Xiong et al, 1996), therefore, we suggest that more studies on both micro-and macroalgae sensitivity to UVB should be conducted, and on the underlying mechanisms resulting in different responses are worthy of further investigation as well.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids are cyclic compounds containing N 2 in a negative oxidation state, and some are known as both toxins and feeding stimulants for insects and as feeding deterrents for mammals (Croteau et al 2000;Hartmann 1991). To date, only a few studies have evaluated the effects of UV-B radiation on alkaloid synthesis, and both positive (Lindroth et al 2000) and negative (Larson et al 1990) effects have been observed. Phenolics, such as tannins, flavonoids, and lignins, compose the third group of plant secondary compounds, and some of these have been shown to be estrogenic and to limit the digestion of cell walls, proteins, and carbohydrate digestion (Van Soest 1994).…”
Section: Introductionmentioning
confidence: 97%